Construction project scheduling and control - Mubarak, Saleh A (Wiley, 2015)
This book helps students learn the processes, tools, and techniques used to make projects run smoothly, with expert guidance toward the realities of this complex function. Scheduling encompasses everything from staff requirements and equipment needs to materials delivery and inspections, requiring a deep understanding of the process. For the student interested in construction management, Construction Project Scheduling and Control is an informative text on the field's current best practices.